PENGARUH BOOK TAX DIFFERENCES DAN TINGKAT HUTANG TER-HADAP PERSISTENSI LABA - Ernawati, Linda; Lasdi, Lodovicus (Widya Mandala Surabaya Catholic University, 2012)
Earnings persistence is a measure that describes the ability of the company to maintain the amount of earnings which is got from current time to future time. Earnings persistence is often used as a consideration of earnings quality because earnings persistence is a component of the qualitative characteristics of relevance, namely predictive value. Therefore, quality earnings can show the continuity of earnings so that persistent earnings tend to be stable. This study is aimed to test whether the book tax differences and debt level affect the earnings persistence. The research design which was used was research with the hypothesis. The depend-ent variable of this study the earnings persistence measured by using a regression coefficient of regression between the account-ing income of the current period and the coming period. The independent variable of this study is the book tax differences meas-ured by using dummy variables and debt levels that were measured with debt to asset ratio. The companies that became the object of this research were manufacturing companies listed on the Indonesia Stock Exchange for the period of 2008-2013. The sample were selected by purposive sampling method. The data was analyzed by using multiple regression. The data analysis showed that large positive book tax differences negatively affected earnings persistence, where as large negative book tax differences did not affect earnings persistence. Debt level positively affected earnings persistence.